New York Amish : Life in the Plain Communities of the Empire State - Johnson-Weiner, Karen (Book collections on Project MUSE., 2017)
This book highlights the existence and diversity of Amish communities in New York State, drawing on twenty-five years of observation, participation, interviews, and archival research.